Application of FGD-BCEL loss function in segmenting temporal lobes on localized CT images for radiotherapy - Wen, Xiaobo; Liang, Bing; Zhao, Biao; Hu, Xiaokun; Yuan, Meifang; Hu, Wenchao; Liu, Ting; Yang, Yi; Xing, Dongming (Frontiers in Oncology, 2023)
Objectives: To find a new loss function to automatically segment temporal lobes on localized CT images for radiotherapy with more accuracy and a solution to dealing with the classification of class-imbalanced samples in temporal lobe segmentation. Methods: Localized CT images for radiotherapy of 70 patients with nasopharyngeal carcinoma were selected. Radiation oncologists sketched mask maps. The data set was randomly divided into the training set (n=49), the validation set (n=7), and the test set (n=14). The training set was expanded by rotation, flipping, zooming, and shearing, and the models were evaluated using Dice Similarity Coefficients (DSC), Jaccard Similarity Coefficient (JSC), Positive Predictive Value (PPV), Sensitivity (SE), and Hausdorff Distance (HD). This study presented an improved loss function, Focal Generalized Dice-Binary cross-entropy loss (FGD-BCEL) and compared it with four other loss functions, Dice Loss (DL), Generalized Dice loss (GDL), Tversky Loss (TL), and Focal Tversky Loss (FTL), using the U-Net model framework. Results: With the U-Net model based on FGD-BCEL, the DSC, JSC, PPV, SE, and HD were 0.87 ± 0.11, 0.78 ± 0.11, 0.90 ± 0.10, 0.87 ± 0.13 and 4.11 ± 0.75, respectively. Except for the SE, all the other evaluation metric values of the temporal lobes segmented by the FGD-BCEL-based U-Net model were improved compared to the DL, GDL, TL, and FTL loss function-based U-Net models. Besides, the FGD-BCEL-based U-Net model was morphologically more similar to the mask maps. The over- and under-segmentation was lessened, and it effectively segmented the tiny structures in the upper and lower poles of the temporal lobe with a limited number of samples. Conclusions: For the segmentation of the temporal lobe on localized CT images for radiotherapy, the U-Net model based on the FGD-BCEL can meet the basic clinical requirements and effectively reduce the over- and under-segmentation compared with the U-Net models based on the other four loss functions. However, there still exists some over- and under-segmentation in the results, and further improvement is needed.